PENGARUH DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BERAU: PENGARUH DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BERAU - LISA PUSPITASARI (ECO-BUILD, 2022)
This study aims to obtain a tested explanation of the Effect of General Allocation Funds and Special Allocation Funds on Economic Growth in Berau Regency in 2012-2021. The subject of this research is the government of Berau Regency and the object of this research is the General Allocation Fund and the Special Allocation Fund for Economic Growth. The type of data collected is quantitative data sourced from the Realization Report of the Regional Revenue and Expenditure Budget (APBD). The method used in this study is the Multiple Linear Regression test. The results showed that the General Allocation Fund partially had no significant effect on economic growth in Berau Regency. The Special Allocation Fund partially has a significant effect on economic growth in Berau Regency. The General Allocation Fund and the Special Allocation Fund simultaneously have a significant effect on Economic Growth in Berau Regency.